Compression Effects in Structural Damping in Sandwich Plates - Tuan, Ho Thien; Łukasiewicz, S. (Engineering Transactions, 1978)
In the present paper, we study the thickness-stretch deformation effect in addition to other effects (bending, extentional and thickness-shear) already investigated in the previous paper [1]. An improved theory of sandwich plates is thus established. Numerical results show for small face thickness ratios, there is a rather notable discrepancy between the present theory and that presented in [1], with regard to the damping parameter.